Nonproductive Infection of Guinea Pig Cells with Human Cytomegalovirus - Fioretti, Armanda (1973)
Human cytomegalovirus was capable of adsorbing to and penetrating guinea pig cells, but was unable to replicate new virus. Cultures infected with virus inoculum of high titer showed a cytopathic effect (CPE) characterized by cell rounding. This CPE depended upon the presence of infectious virus, and its extent was directly related to the multiplicity of infection. Staining by indirect immunofluorescence by using human convalescent sera was positive as early as 4 h postinfection. Maximal fluorescence was observed 24 h postinfection when 50% of the cells contained fluorescent antigens both in nuclei and cytoplasm. No evidence for viral replication was found, and no defective particles were detected by electron microscopy. Treatment with actinomycin D or with cycloheximide strongly inhibited both the fluorescent antigens and the CPE, whereas 5-fluorodeoxyuridine and bromodeoxyuridine were ineffective.